Economic Freedom and the Affordable Care Act: Medicaid Expansions and Labor Mobility by Race and Ethnicity. (March 2018) - Callison, Kevin; Sicilian, Paul
A greater level of government involvement in the financing of health care is generally viewed unfavorably by organizations monitoring economic freedom. However, increased government provision of health insurance could be associated with improved economic freedom through enhanced labor market mobility. For example, job-lock alleviation accompanying a public insurance expansion could lead to increased innovation or a higher likelihood of self-employment. In this article, we use the Affordable Care Act (ACA)'s recent Medicaid expansions to examine the effect of an increase in public health insurance provision on labor market outcomes by gender and race/ethnicity. Our results lend support to the notion that state Medicaid expansions are associated with improved labor market autonomy for white men and white women; however, we find mixed results for black and Hispanic men and women. Notably, our findings cast doubt on earlier claims that the ACA would lead to large reductions in labor force participation and employment.